Nanocompósitos MWCNT/Nb₂O₅ e MWCNT/TiO₂: Síntese, Caracterização e Aplicação em Sensores Eletroquímicos - RAFAEL HENRIQUE DE OLIVEIRA (2023)
Electrochemical sensors play a crucial role in the accurate detection of chemical compounds in various areas, including clinical analysis and environmental monitoring. In this context, nanocomposites of carbonaceous materials and metal oxides have emerged as highly promising materials. This work aims to synthesize and characterize nanocomposites for application in electrochemical sensors. A new nanocomposite was obtained by decorating multi-walled carbon nanotubes (MWCNTs) with Nb₂O₅ using the peroxide oxidative complex method (OPM) combined with hydrothermal treatment. Additionally, the nanocomposite with MWCNTs and TiO₂ was obtained by the solvothermal method. The materials were characterized using techniques such as scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The nanocomposites were used as modifiers of glassy carbon electrodes (GCE) in the fabrication of GCE/MWCNT/Nb₂O₅ and GCE/MWCNT/TiO₂ sensors. The electrochemical response of these sensors was evaluated through cyclic voltammetry (CV) in solutions such as H₂SO₄ (pH 2.0) and Britton-Robinson buffer solution (pH 7.0). The sensors demonstrated promising sensitivity and selectivity in the detection of H₂O₂ and paracetamol in an aqueous medium. By means of cyclic voltammetry, the GCE/MWCNT/Nb₂O₅ sensor exhibited a detection limit (LD) of 1.5 μM and a quantification limit (LQ) of 5.0 μM for H₂O₂. The GCE/MWCNT/TiO₂ sensor revealed an LD of 4.0 μM and an LQ of 14.0 μM. The electrocatalytic activity of the GCE/MWCNT/Nb₂O₅ sensor in paracetamol detection, even in the presence of interferents such as epinephrine and tryptophan, was also remarkable. Square wave voltammetry achieved an LD of 0.11 nM and an LQ of 0.49 nM, surpassing previous studies. These results indicate the potential of these nanocomposites as materials for the development of more efficient electrochemical sensors, with promising application in clinical and environmental samples.